Steroid Compounds From Gynura pseudochina (Lour) DC - Ferlinahayati Ferlinahayati; Roby Pahala J Gultom; Herlina Herlina; Eliza Eliza (Universitas Jenderal Soedirman, 2017)
Daun dewa (Gynura pseudochina Lour DC) is a one of popular traditional medicine to treat various diseases. This research was conducted to isolate chemical compounds from daun dewa leaves using various chromatographic techniques. A steroid mixture namely b-sitosterol (1a) and stigmasterol (1b) were isolated for the first time from the methanol extract of daun dewa. The structures were determined base on spectral evidence including IR, NMR 1D and NMR 2D.